1996
DOI: 10.1002/prep.19960210509
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser Induced Decomposition of Energetic Polymers: Comparison of ultraviolet (355 nm) and infrared (9.3 μm) initiation

Abstract: Irradiation of the energetic polymer GAP (glycidyl azido polymer) by a high power pulsed UV laser leads to its rapid decomposition. A large amount of solid and gaseous material is released, and in the presence of an inert gas, a shock wave develops. Comparison with an inert polymer indicates that the energy released by the exothermicity of the decomposition reaction contributes significantly to the shock formative energy. The energy released in the micro‐explosion can be estimated from the analysis of the shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Some work focuses on propellants and pyrotechnics (Assovskii & Leipunskii 1980;Haas et al . 1994;Haas & ben Eliahu 1996;Østmark & Roman 1993;Radenac et al . 1998;Saito et al .…”
Section: Ignition or Initiation By Direct Irradiation (A) Early Researchmentioning
confidence: 99%
“…Some work focuses on propellants and pyrotechnics (Assovskii & Leipunskii 1980;Haas et al . 1994;Haas & ben Eliahu 1996;Østmark & Roman 1993;Radenac et al . 1998;Saito et al .…”
Section: Ignition or Initiation By Direct Irradiation (A) Early Researchmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, a few studies found that a laser ablated energetic polymer (glycidyl azide polymer [GAP]) produced a faster shock wave than nonenergetic polymers. [16][17][18][19] The increased shock wave velocity was attributed to the higher decomposition enthalpy of GAP; the pulsed laser initiated a self-sustaining exothermic reaction resulting in rapid formation of gaseous products. More recently, Roy et al 20 measured spatially and temporally resolved temperatures behind an expanding laser-induced shock wave to demonstrate differences in energy release between reacting aluminum nanoparticle formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from degradation in solution, the pulsed‐laser technique has been used to study the photoetching, ablation, and deposition of polymer thin films onto surfaces 23–26. The theoretical model for the process of ablation considers it to be a nonstationary thermodestruction process that follows an Arrhenius equation, where degradation occurs for every laser pulse 27.…”
Section: Introductionmentioning
confidence: 99%